Aquí se contienen cuatro obras muy santas, todas expurgadas y atribuidas a Joan Timoneda. - CLIMENT, JOAN MAHIQUES; ROVIRA I CERDÀ, HELENA (Scripta, 2013)
We study and edit four Spanish poems with the following opening lines: 1) Digas, hortelano; 2) A vos, Virgen pía, estrella que guía; 3) Yo conozco, digo y cuento; 4) Oíd, reina que al cielo. The earliest known edition that includes all of them was published sine notis (but probably in Valencia from 1561 to 1563) with a rubric that attributed the first work to Joan Timoneda, the third one to Francisco de Argüello and the last one to Ángel González. Some later literary sources and indexes of forbidden books consider that the four pieces were composed by Joan Timoneda, at whom Pere Salvà i Mallén assigned more specifically the second poem, titled Pavana de Nuestra Señora, although it was printed in a chapbook datable circa 1533-1535 and therefore it seems written prior to Timoneda's output. These four pieces were published together in chapbook form during the sixteenth and seventeenth centuries, but there is no evidence of its printed transmission during the eighteenth century, just when they were expurgated. We describe some known printed books and manuscripts transmitting these poems, and we relate them to another poetic works emerged in mid-sixteenth century Valencia